2008
DOI: 10.1155/2008/738101
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Alters Contraction‐Induced Mitogen Activated Protein Kinase Activation in the Rat Soleus and Plantaris

Abstract: The prescription of anaerobic exercise has recently been advocated for the management of diabetes; however exercise-induced signaling in diabetic muscle remains largely unexplored. Evidence from exercise studies in nondiabetics suggests that the extracellular-signal-regulated kinases (Erk1/2), p38, and c-JUN NH2-terminal kinase (Jnk) mitogen-activated protein kinases (MAPKs) are important regulators of muscle adaptation. Here, we compare the basal and the in situ contraction-induced phosphorylation of Erk1/2- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Verification of transfer efficiency and equal loading of protein among lanes was determined by Ponceau S. Immunodetection of antigens was performed as described previously [34,35]. In brief, membranes were blocked for 1 h at room temperature with constant shaking in blocking buffer (5% non-fat dry milk in TBS-T (20mM Tris-base, 150mM NaCl, 0.05% Tween-20), pH 7.6) followed by serial washes in TBS-T at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Verification of transfer efficiency and equal loading of protein among lanes was determined by Ponceau S. Immunodetection of antigens was performed as described previously [34,35]. In brief, membranes were blocked for 1 h at room temperature with constant shaking in blocking buffer (5% non-fat dry milk in TBS-T (20mM Tris-base, 150mM NaCl, 0.05% Tween-20), pH 7.6) followed by serial washes in TBS-T at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…ALTHOUGH PHYSICAL ACTIVITY is an effective, low-cost, and nonpharmacological alternative to traditional prevention and treatment methods for insulin resistance syndrome (40,41), insulin-resistant skeletal muscle may be "desensitized" to the anabolic action of exercise (14,37,38,47,51,59,63). Considering the putative role of mitochondria in the development and progression of insulin resistance syndrome (49), the contractile activity-induced response of the organelle in metabolic disease states is of particular interest (34).…”
mentioning
confidence: 99%
“…Although augmentations of mitochondrial protein synthesis rates appear to dissipate after the initial RE bout in young individuals (66), older adults exhibit a sustained increase in the translational capacity of mitochondrial proteins even after several months of resistance training (46,61). Despite clinically significant improvements in risk factors associated with insulin resistance syndrome following longterm participation in moderate-intensity resistance exercise (10,12,17,62), several studies indicate that insulin resistance (and/or related comorbidities) may limit gains in muscle mass (51,59) and strength (35) by altering anabolic signaling events following resistance-type contractile activity (37,38,51). Paturi et al (51) recently reported an attenuated hypertrophic response in soleus muscle following synergistic ablation of gastrocnemius and plantaris in the obese Zucker rat (fa/fa), a widely recognized model of genetic obesity and insulin resistance syndrome.…”
mentioning
confidence: 99%
“…Previous data from our laboratory have suggested that the capacity of the OZ soleus muscle to undergo hypertrophy in response to increased loading is diminished compared with that observed in the lean Zucker (LZ) rat. Why metabolic syndrome may affect the hypertrophic response of muscle is not clear although we and others have noted that insulin resistance is associated with differences in the ability of skeletal muscle to activate intracellular signaling cascades in response to alterations in contractile activity (14,19,20,34).…”
mentioning
confidence: 99%